PENGARUH PERBEDAAN ANTARA LABA AKUNTANSI DAN LABA FISKAL TERHADAP PERSISTENSI LABA PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA - Hasan, Mudrika Alamsyah; Purwanti, Sheila Nika (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study aims to obtain empirical evidence about the relationship between book-tax differences and earning persistence in the financial statements of listedcompanies in Indonesian Stock Exchange. This study uses the technique ofPurposive Sampling Method, selected sample of 50 companies during the period of2007-2010. Methods of analysis used in this study is the technique of multipleregression analysis version 17.0. Variables that used in this research are earningbefore income tax next period as Y and earnings before tax at this period. as X. Thisresearch also using book tax differents as moderating variable. From the results oftesting that has been done, the simultaneous regression test (F test) showed that allthe independent variables studied had a significant effect on the variable earningpersistence. Partial regression test (t test) showed that the variables of PTBIt,LNBTD*PTBIt and LPBTD*PTBIt affect the variable earning persistence. The2magnitude of the effect caused by Adjusted R by all independent variables together86,4% of the dependent variable, while the remaining 13.6% is influenced by othervariables not examined in this study.Keyword : accounting profit,taxable income, and income peristensi